2016
DOI: 10.1093/sleep/zsw042
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Impact of Successive Cycles of Sleep Restriction With and Without Naps in Adolescents

Abstract: Study Objectives:To characterize adolescents’ neurobehavioral changes during two cycles of restricted and recovery sleep and to examine the effectiveness of afternoon naps in ameliorating neurobehavioral deficits associated with multiple nights of sleep restriction.Methods:Fifty-seven healthy adolescents (aged 15–19 years; 31 males) participated in a parallel group study. They underwent two cycles of sleep restriction (5-hr time in bed [TIB] for five and three nights in the first and the second cycles, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 48 publications
9
59
1
Order By: Relevance
“…Details of the nap durations are reported in Lo et al . (). In brief, PSG assessment showed that the nap group slept 37–53 min more than the no‐nap group each day ( P < 0.001), incurring a lower sleep debt over the course of the protocol.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Details of the nap durations are reported in Lo et al . (). In brief, PSG assessment showed that the nap group slept 37–53 min more than the no‐nap group each day ( P < 0.001), incurring a lower sleep debt over the course of the protocol.…”
Section: Resultsmentioning
confidence: 97%
“…Details of this protocol are reported in Lo et al . (). The protocol for this study was approved by the Institutional Review Board of the National University of Singapore, and all participants signed written informed consent.…”
Section: Methodsmentioning
confidence: 97%
“…Data were acquired from adolescents participating in two protocols – the Need for Sleep Studies (NFS) 1 and 2 (Lo, Ong, Leong, Gooley, & Chee, ; Lo et al., ; Ong, Lo, Gooley, & Chee, , ). Participants met the following screening criteria: (i) between 15 and 19 years old; (ii) no history of chronic medical conditions, psychiatric illness or sleep disorders; (iii) a body mass index (BMI) of ≤ 30 kg m −2 ; (4) not habitual short sleepers (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…not individuals who both [a] had an average actigraphically assessed TIB of < 6 hr; and [b] showed no sign of sleep extension for more than 1 hr on weekend compared with weekday nights); (v) daily consumption of fewer than five cups of caffeinated beverages; and (vi) no history of travel across more than two time zones 1 month prior to the experiment. Full details of the recruitment and screening criteria are detailed in our earlier work (Lo et al., , ). The study was approved by the Institutional Review Board of the National University of Singapore, and informed consent was obtained from both participants and their legal guardian.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation